Analisis Kesalahan Ejaan dan Tata Bahasa dalam Karya Ilmiah Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia - Upaya Bakti Murni Gulo; Agusnita Zebua; Bezisokhi Gulo; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2024)
The aim of this research is to describe the types of spelling and grammatical errors found in the scientific work of students in the Indonesian Language and Literature Education Study Program. This research uses qualitative methods with a data analysis approach. The data collection procedure in this research was carried out using the reading and note-taking method. The results of the research show that the articles of Indonesian language and literature education study program students are classified into three categories, namely (1) writing 24 basic words, (2) writing 9 words with affixes, (3) writing 19 words in capital letters, (4) writing 3 words of numbers and numbers, (5) writing 10 words of pronouns, (6) writing 3 words of loanwords, (6) writing 4 words in italics, (7) using 1 word sentences, (8) use of 5 words of punctuation, (9) use of 11 words.